2018
DOI: 10.1108/ijqss-10-2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of value-adding services on quality, loyalty and brand equity in the brewing industry

Abstract: PurposeThe purpose of this research is to investigate the impact of logistics value-adding services and perceived service quality on brand equity among B2B customers of a brewery company. Design/methodology/approachA theoretical model is developed and tested using survey data from 173 hotel, restaurant and catering industry customers of a brewery company in Finland. FindingsValue-adding services play an important role in building the brewery company's brand equity through perceived service quality. Besides a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
(72 reference statements)
0
19
0
1
Order By: Relevance
“…Empirical studies have demonstrated that the higher the brand equity, the greater the loyalty [16][17][18]. A brand is likely to have positive brand equity if it receives more favorable responses, that is, higher levels of brand association, awareness, preference, and familiarity [55].…”
Section: Brand Equity Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies have demonstrated that the higher the brand equity, the greater the loyalty [16][17][18]. A brand is likely to have positive brand equity if it receives more favorable responses, that is, higher levels of brand association, awareness, preference, and familiarity [55].…”
Section: Brand Equity Theorymentioning
confidence: 99%
“…The marketing efforts of cultural organizations tend to be focused on sustaining and creating loyalty [15], which can be affected by brand equity [16][17][18]. Customer-based brand equity (CBBE), which can be defined as the added value of a brand to a customer [19], is said to reinforce brand loyalty and brand preference, attract new customers, and generate greater resiliency to competitors' marketing actions, enabling the brand to earn consistent, predictable, and higher market shares over time [20].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have demonstrated that the higher the brand equity, the greater the loyalty [13,14,15]. A brand is likely to have positive brand equity if it receives more favorable responses, that is, higher levels of brand association, awareness, preference, and familiarity [47].…”
Section: Brand Equity Theorymentioning
confidence: 99%
“…In addition, the model considered brand identity, brand meaning, its unique associations, brand response with consumer evaluations, and brand-consumer relationship, including brand loyalty [37]. Both concepts were analyzed for different markets and modified for product brands [38][39][40][41], retail brands [42,43], and service brands [44][45][46][47]. BE for product brands was analyzed in such categories as sport clothes and shoes [48], cars [49], TV [48,49], and service brands, such as hotels [50][51][52][53][54][55][56][57][58], airlines [59][60][61], and restaurants [57,[62][63][64].…”
Section: Introductionmentioning
confidence: 99%